ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2023
DOI: 10.1109/icassp49357.2023.10095816
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Independent Component Analysis Based on Entropy Bound Minimization for Subgroup Identification from Multi-subject fMRI Data

Abstract: Identification of subgroups of subjects homogeneous functional networks is a key step for precision medicine. Independent vector analysis (IVA) is shown to be effective for this task, however, it has a substantial computing cost. We propose a constrained independent component analysis algorithm based on minimizing the entropy bound (c-EBM) to overcome the computational complexity limitation of IVA. A set of spatial maps used as constraints provides a connection across the datasets, provides alignment across su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Our findings indicate the IVA-S3 offers the potential for improved subgroup identification with fMRI data, as we demonstrated that the IVA-S3 is able to better preserve subject variability. A more detailed investigation of subgroup identification is beyond the scope of this work but is an emerging new area of research [4,[42][43][44][45]. Furthermore, as discussed in the previous section, the IVA might be prone to overfitting when analyzing large numbers of datasets.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings indicate the IVA-S3 offers the potential for improved subgroup identification with fMRI data, as we demonstrated that the IVA-S3 is able to better preserve subject variability. A more detailed investigation of subgroup identification is beyond the scope of this work but is an emerging new area of research [4,[42][43][44][45]. Furthermore, as discussed in the previous section, the IVA might be prone to overfitting when analyzing large numbers of datasets.…”
Section: Discussionmentioning
confidence: 98%